2011
DOI: 10.1111/j.1600-0897.2011.01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative Emotions and Cytokines in Maternal and Cord Serum at Preterm Birth

Abstract: The findings indicate associations in preterm delivery between negative emotions and both maternal and neonate immune activity. Future studies should investigate whether such associations are part of the etiology of preterm delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 47 publications
0
26
0
2
Order By: Relevance
“…Finally, Fransson et al (2012) measured the relationship between maternal emotions and cytokines at birth in both maternal serum and cord blood, and whether those parameters differed between women who delivered preterm and those who delivered at term. The sample included 27 women who delivered preterm and 37 who delivered at term.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Fransson et al (2012) measured the relationship between maternal emotions and cytokines at birth in both maternal serum and cord blood, and whether those parameters differed between women who delivered preterm and those who delivered at term. The sample included 27 women who delivered preterm and 37 who delivered at term.…”
Section: Resultsmentioning
confidence: 99%
“…The Kondo et al (2011) and Fransson et al (2012) studies, most recent of this group, did avoid some of the limitations of the earlier work in this subset. The Kondo et al study has a relatively large sample size, controls for possible confounders such as smoking, alcohol use, and history of allergic disease, and is highly representative (the sample includes all lactating mothers in the city).…”
Section: Discussionmentioning
confidence: 99%
“…However, HGF have been reported elevated in older adults with subclinical symptoms of depression (Arnold et al, ). Moreover, elevated levels of IL‐18 have been reported in response to delivery in women with depressive symptoms during pregnancy (Fransson et al, ). Increased IL‐18 has also been associated with poststroke depression (Yang et al, ), while IL‐18 levels have been reported to be lower in depressed patients with chronic disease (Bossu et al, ; Fan, Luo, Ou, & He, ).…”
Section: Discussionmentioning
confidence: 99%
“…Corwin et al (3 rd trimester and multiple postpartum timepoints, N=152) 69 found no association of IL-1β with depressive symptoms. Fransson et al (at delivery, N=64) 64 found no association of IL-1α in cord serum with maternal depressive symptoms. (This group attempted to measure both IL-1α and IL-1β in maternal serum at delivery as well but found both below the limit of detection of their assay.…”
Section: Depression and Inflammation In The Perinatal Periodmentioning
confidence: 94%